Perceptions On Recurrent Drought Incidents By Households In Janamora District, North Gondar Zone, Amhara Region, Ethiopia. - Yimam, Mr. Dereje Amene; Zeleke, Dr. Menberu Teshome; Krishnaiah, Dr. Pujari (International Journal of Scientific Research and Management (IJSRM), 2018)
Recurring drought is a major challenge in the Drought Prone Area of Janamora in North Ethiopia. Rainfed agriculture is the major income activity of over 91% of the district's population. The objective of this study was to understand the rural farming community's perception of drought impacts on their livelihood status and their coping strategies at household level. This study was based on both primary and secondary data collected through a survey of 334 farming households and 35 years of precipitation and temperature data retrieved from National Meteorology Agency of Ethiopia. The results elucidated that the mean annual rain fall was 786.2mm and variability for years 1979-2013 reaches 27.2% at Janamora district. The variation of monthly maximum temperature was found to be CV% of 16.2% at Janamora district. The results indicated that more than  80% of farmers believed that temperature in the district had become warmer and over 90% were of the opinion that rainfall timing had changed, resulting in increased frequency of drought. Their perception conforms to measured precipitation and temperature trends in the district. Thus, the government should design policies aimed at improving these factors.